2016
DOI: 10.1017/jfm.2015.693
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Lagrangian model for hydrodynamic acceleration of inertial particles in gas–solid suspensions

Abstract: The acceleration of an inertial particle in a gas-solid flow arises from the particle's interaction with the gas and from interparticle interactions such as collisions. Analytical treatments to derive a particle acceleration model are difficult outside the Stokes flow regime, but for moderate Reynolds numbers (based on the mean slip velocity between gas and particles) particle-resolved direct numerical simulation (PR-DNS) is a viable tool for model development. In this study, PR-DNS of freely-evolving gas-soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(97 citation statements)
references
References 46 publications
14
82
1
Order By: Relevance
“…This family of curves asymptotes to a Heaviside function in the Reynolds number up to 100. For this case, the particle granular temperature is approximately in the range of 0.064m 2 /s 2 to 2.728m 2 /s 2 (Tenneti et al, 2016). If we assume that the Hamaker constant is A = 10 −19 J, the solidphase density ratio is 400, and the minimum particle separation is d 0 = 2 Angstrom, then the minimum and maximum values of Ha for the particles suspended in an air flow would be Ha min = 3×10 −5 and Ha max = 1.2×10 −3 , respectively.…”
Section: Drag Model: Transition Between Uniform and Clustered Drag Lawsmentioning
confidence: 89%
See 1 more Smart Citation
“…This family of curves asymptotes to a Heaviside function in the Reynolds number up to 100. For this case, the particle granular temperature is approximately in the range of 0.064m 2 /s 2 to 2.728m 2 /s 2 (Tenneti et al, 2016). If we assume that the Hamaker constant is A = 10 −19 J, the solidphase density ratio is 400, and the minimum particle separation is d 0 = 2 Angstrom, then the minimum and maximum values of Ha for the particles suspended in an air flow would be Ha min = 3×10 −5 and Ha max = 1.2×10 −3 , respectively.…”
Section: Drag Model: Transition Between Uniform and Clustered Drag Lawsmentioning
confidence: 89%
“…Now if we assume that in Eq. 4 the maximum overlap δ is 1% of the particle diameter d p and also assume that the granular temperature in gas-solid flow scales as T / | W | 2 ∼ 10 −2 (Tenneti et al, 2016), it can be concluded from Eq. 4 that the contact to fluid timescales ratio is…”
Section: Analysis Of Numerical Constraintsmentioning
confidence: 96%
“…This method is shown to be accurate and numerically convergent (Garg et al, 2010;Tenneti et al, 2011). In addition, PUReIBM has been successfully used to simulate fixed particle assemblies (Tenneti et al, 2010(Tenneti et al, , 2011Sun et al, 2015) and freely evolving suspensions of monodisperse gas-solid flows (Subramaniam et al, 2014;Mehrabadi et al, 2015;Tenneti et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This method is shown to be accurate and numerically convergent (Garg et al, 2010c;Tenneti et al, 2011). In addition, PUReIBM has been successfully used to simulate fixed particle assemblies (Tenneti et al, 2010(Tenneti et al, , 2011Sun et al, 2015) and freely evolving suspensions of monodisperse gas-solid flows (Subramaniam et al, 2014;Mehrabadi et al, 2015;Tenneti et al, 2016). The extension of the PUReIBM formulation to account for polydisperse gas-solid suspensions is straightforward (see C).…”
Section: Methodsmentioning
confidence: 98%
“…The difference between the net mean velocity of the two particle classes contributes to the relative particle mass flux that is the signature of particle segregation. On the other hand, the interaction of particles with flow structures gives rise to generation of particle velocity fluctuations (Tenneti et al, 2016) that are characterized by a non-zero level of kinetic energy. If the particle suspension is dense, then the probability of particle collisions increases with increase of particle velocity fluctuations.…”
Section: Introductionmentioning
confidence: 99%